Determinants of Sustainability Report Disclosure in Financial Companies - Suharni, Suharni; Nor, Wahyudin (Economic Education Analysis Journal, 2023)
The purpose of this study was to examine and analyze the influence of human resource slack, gender diversity, feminism of the board of directors, feminism of the board of commissioners and sustainability officer on the disclosure of the Sustainability Report. The population for this research is financial sector companies listed on the Indonesia Stock Exchange during the period 2019 to 2021. The research sample selection method used is purposive sampling. This study used descriptive statistical analysis and logistic regression analysis, using SPSS data processing software version 26 as an analysis tool. The results of the study show that feminism of the board of directors influences the disclosure of the Sustainability Report positively and significantly. In addition, the results also show that gender diversity affects the disclosure of the Sustainability Report in a negatively significant manner, henceforth human resources slack, feminism of the board of commissioners and the sustainability officer does not affect the disclosure of the Sustainability Report. This study contributes to management accounting research by increasing understanding of the factors that influence the disclosure of Sustainability Report in financial sector companies.